FORMULATION OF SUNSCREEN BODY LOTION FROM MORINGA ( Moringa oleifera L.) LEAF EXTRACT - Desi Adriyanti Nina Taebenu Taebenu; Ni Luh Arpiwi; Ni Wayan Sudatri (Universitas Airlangga, 2023)
The way to avoid UV radiation is to use sunscreen lotion. Moringa plant (Moringa oleifera L.) contains 46 types of antioxidants and 36 anti-inflammatory compounds that have the potential as sunscreens. The purpose of this study was to determine the effect of the type of concentration of Moringa leaf extract on the SPF value, to analyze the quality of the lotion produced and the level of probandus preference for sunscreen lotions. The research was conducted at the Laboratory of Plant Physiology, FMIPA Unud, Laboratory of Chemical Analysis and Pharmaceutical Analysis, FMIPA Unud, and the Integrated Research Laboratory of Unud. The design used in this study was a completely randomized design (CRD) using 0% concentration of Moringa leaf extract; 0.5%; 1%; 1.5% and 2%. Parameters tested include; organoleptic test, homogeneity, pH, viscosity, hedonic and the determination of SPF number with in vitro technique. The results of the study show that the pH, homogeneity and viscosity tests of F0, F1, F2, F3 and F4 have met the requirements of SNI. The SPF value of each formula is 5.6780; 9.7605; 19.0299; 38.0369; 68.8832. Statistical analysis of pH and viscosity showed that there were different variations in each formulation. Statistical analysis of the hedonic test showed that there was no difference in variation in each formulation. As the addition of moringa leaf extract to sunscreen lotion, the higher the SPF number.